2018
DOI: 10.4236/as.2018.97061
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Manganese Fertilization and the Effects on Millet Seed Yield, Seed Quality, and Forage Potential of Residual Stalks

Abstract: Millets are important natural grain source for wild and game birds and the domesticated varieties are good sources of grain for human and livestock nutrition as well as summer forage. Unlike sorghum, millet seed has less anti-nutrient factors and is a better choice for animal feed formulations. Pearl millet is an example of such millets and has both forage-and grain-type varieties. However, opportunities exist for dual use of millet for grain and residue for forage. In this study two millets: Pennisetum glaucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Indeed, the application of potassium at optimal dose has a positive impact on water use efficiency of maize [26] thus improving its growth [27] and allows vigorous growth and early flowering of tomato [28]. Kering and Broderic [29] showed that millet plant growth was maximal around 80 kg K 2 O/ha and above this dose the plants were shorter.…”
Section: Strawberry Growth Parametersmentioning
confidence: 99%
“…Indeed, the application of potassium at optimal dose has a positive impact on water use efficiency of maize [26] thus improving its growth [27] and allows vigorous growth and early flowering of tomato [28]. Kering and Broderic [29] showed that millet plant growth was maximal around 80 kg K 2 O/ha and above this dose the plants were shorter.…”
Section: Strawberry Growth Parametersmentioning
confidence: 99%
“…Therefore, BTM can be considered as a dietary component which may support the prevention and management of certain non-communicable diseases (Kishore et al, 2021). The residual stalk including stem and leaves after harvesting the BTM (Panicum ramosum L.) is used as livestock feed because it contains 56.7 g/kg of crude protein and 594.2 g/kg of total digestible nutrient (Kering and Broderick, 2018) along with higher level of minerals like magnesium (5.9 g/kg), phosphorus (1.5 g/kg), and calcium (9.0 g/kg). High fiber content and presence of some anti-nutritional factors like phytates and tannins in millets affect bioavailability of minerals but these compounds are limited to millet seed coat which can be removed during processing (Ramashia et al, 2019).…”
Section: Nutritional Attributesmentioning
confidence: 99%
“…Current recommended dietary allowances have been published by the National Academy of Science (2019a; 2019b). Average pearl millet grain nutrient concentrations for West Afeica (van Duivenbooden, 1992), Mali, Niger, Nigeria, and Tanzania (Wortmann et al, 2018), the United States (Kering and Broderick (2018), and worldwide (Kumar et al, 2018) have been published.…”
Section: Introductionmentioning
confidence: 99%